Men, Work, and Mental Health: A Systematic Review of Depression in Male-dominated Industries and Occupations - Ann M. Roche; Ken Pidd; Jane A. Fischer; Nicole Lee; Anje Scarfe; Victoria Kostadinov (Elsevier, 2016)
Among men, depression is often unrecognised and untreated. Men employed in male-dominated industries and occupations may be particularly vulnerable. However, efforts to develop tailored workplace interventions are hampered by lack of prevalence data. A systematic review of studies reporting prevalence rates for depression in male dominated workforce groups was undertaken. Studies were included if they were published between 1990 - June 2012 in English, examined adult workers in male-dominated industries or occupations (> 70% male workforce), and used clinically relevant indicators of depression. Twenty studies met these criteria. Prevalence of depression ranged from 0.0% to 28.0%. Five studies reported significantly lower prevalence rates for mental disorders among male-dominated workforce groups than comparison populations, while six reported significantly higher rates. Eight studies additionally found significantly higher levels of depression in male-dominated groups than comparable national data. Overall, the majority of studies found higher levels of depression among workers in male-dominated workforce groups. There is a need to address the mental health of workers in male-dominated groups. The workplace provides an important but often overlooked setting to develop tailored strategies for vulnerable groups.